INOVASI, KUALITAS PELAYANAN DRIVER DAN E-SERVICESCAPE TERHADAP KEPUTUSAN PENGGUNAAN GO-JEK DI SURAKARTA - Syam Ma’arip Aiddul Fitra; Eny Kustiyah; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
The studyaaims to analyzeathe effect ofapartial or simultaneous innovation, driver service quality and e-servicescape on the decision to use Go-jek in Surakarta, Central Java. Thisatype ofaresearch isaquantitative. Theapopulation of thisastudy areathose who are Go-jek users in Surakarta. In this study the sample obtained by 100 respondents. Data obtained from the questionnaire using accidental sampling samplingatechnique. Inathisastudy using multiplealinear regressionaanalysis.Thearesults ofathe studyashow innovation, the quality of driver services and e-servicescape simultaneously or partially influence the decision to use Go-jek in Surakarta. Keywords: Innovation, Service quality, E-servicescape, Decision of Use